Learning Mandarin Endocentric Phrases: A Case Study of Malaysian University Students - Mok Soon Sim (Universitas Negeri Malang, 2024)
The Mandarin language is becoming increasingly popular in the education sector in Malaysia. Universiti Teknologi MARA (UiTM) has the largest number of Malay students studying Mandarin in the country. Almost all Malay students studying Mandarin at the university do not have a background in Mandarin. They are inevitably influenced by their mother tongue, Malay. The purpose of this study is to analyze the common Mandarin biased phrasal errors made by Malay students learning Mandarin at UiTM. In addition, some teaching methods are recommended to guide the Mandarin teaching staff. This study was conducted using mixed methods. Two research instruments were used in this study, i.e., questionnaires and interviews. Forty Malay students who were enrolled in the Introductory Mandarin Level 2 course at UiTM Shah Alam Campus were selected as survey respondents. The results of the study indicated that respondents made four common errors in learning Mandarin biased phrases, namely: (i) omission of quantifiers, (ii) reversal of the order of biased phrase strings, (iii) incorrect use of demonstrative pronouns, and (iv) excessive use of the particle “de”. The Mandarin teachers can use a variety of methods to teach Mandarin biased phrases, including comparisons with English, and implementing interactive, collaborative and innovative learning in the classroom. In the future, researchers can further study the grammatical errors made by Malay students with different educational backgrounds or language levels in learning Mandarin in order to develop more targeted teaching strategies for students with different levels of proficiency.